Strategi Desain Label Kemasan dan Positioning Produk UMKM Kawasan Ekosistem Mangrove di Desa Tengin Baru - Panggulu Ahmad Ramadhani Utoro; Nurul Puspita Palupi; Yulian Andriyani; Marwati Marwati; Maulida Rachmawati; Esti Handayani Hardi; Rita Diana; Haris Retno Susmiyati (Fakultas Kehutanan dan Lingkungan Tropis, Universitas Mulawarman, 2023)
ABSTRACT Micro, Small, and Medium Enterprises (MSMEs) are the backbone of the country's economy, particularly in Indonesia. Instructions to improve the quality and modernization of cooperatives and MSMEs in efforts to build an inclusive economy have been issued by the President of the Republic of Indonesia. MSMEs face increasing challenges in the face of global markets and digitalization. The use of technology has become one of the skills that MSME players must master, in addition to finance and investment. To face all of this, improving MSME productivity can be achieved through proper positioning and design on packaging labels. Increasing sales needs to be approached with the creativity of MSME players in utilizing existing technology. Product photos can increase consumer purchasing interest. Presenting attractive photos that are genuine images of the products being sold provides added value to increase consumer purchasing interest in the product, especially in the food sector. This training activity was carried out in Tengin Baru Village, Sepaku District, Penajam Paser Utara Regency. Target of this activity is the community and MSME players in the mangrove ecosystem area and close to the National Capital Region (NCR) of Nusantara. The goal of this activity is to increase understanding of the function of label design and product positioning as well as product photos in improving product quality and increasing consumer purchasing interest. The results of the training have a significant effect on increasing the insights of the community, especially MSME players, in the function of packaging label design and product photos. Keywords: Design; Label; Packaging; Product Image; MSMEs ABSTRAK Usaha Mikro, Kecil dan Menengah (UMKM) merupakan ujung tombak dari perekonomian negara, khususnya Indonesia. Instruksi untuk peningkatan kualitas dan modernisasi koperasi serta UMKM dalam upaya membangun ekonomi inkusif telah dilakukan oleh Presiden Republik Indonesia. Tantangan UMKM semakin besar dengan dihadapkan kepada pasar global dan digitalisai. Pengusaan teknologi menjadi salah satu skill yang harus dikuasai oleh para pelaku UMKM. Selain keuangan dan investasi. Untuk mengadapi semua itu, dalam meningkatkan produktivitas UMKM dapat melalui positoning yag tepat dan desain pada label kemasan. Peningkatan penjualan perlu didekati dengan kreativitas para pelaku UMKM dalam memanfaatan teknologi yang sudah ada. Foto Produk dapat meningkatkan minat beli konsumen. Penyajian foto yang menarik dan merupakan gambar asli dari produk yang akan dijual menjadi nilai tambah tersendiri untuk meningkatkan minat beli konsumen terhadap produk tersebut. Terutama pada produk pangan. Kegiatan pelatihan ini di laksanakan di Desa Tengin Baru, Kecamatan Sepaku, Kabupaten Penajam Paser Utara. Sasaran kegiatan ini adalah masyarakat dan pelaku UMKM di kawasan ekosistem mangrove dan dekat dengan kawasan Ibu Kota Negara (IKN) Nusantara. Sedangkan tujuan dari kegiatan ini adalah untuk meningkatkan pemahaman tentang fungsi desain label dan positoning produk serta foto produk dalam meningkatkan kualitas produk dan meningkatkan minat beli dari konsumen. Hasil dari pelatihan memberikan efek yang cukup signifikan terhadap penambahawan wawasan dari masyarakat khususnya pelaku UMKM dalam fungsi desain label kemasan dan foto produk. Kata kunci: Desain; Foto Produk; Kemasan; Label, UMKM